Renal Evaluation in Common Variable Immunodeficiency - Giovany Gomes Capistrano; Gdayllon Cavalcante Meneses; Fernanda Macedo de Oliveira Neves; Renata de Almeida Leitão; Alice Maria Costa Martins; Alexandre Braga Libório (Journal of Immunology Research)
Introduction. Common variable immunodeficiency (CVID) comprises a heterogeneous group of disorders characterized by impaired antibody production. Kidney involvement in CVID is described in isolated and sporadic case reports. The objective of this study was to study the renal function pattern in CVID patients through glomerular and tubular function tests. Methods. Study of 12 patients with CVID diagnosis and 12 healthy control individuals. Glomerular filtration rate (GFR), fractional excretion of sodium (FENa+) and potassium (FEK+), urinary concentration, and acidification capacity were measured. In addition, microalbuminuria and urinary monocyte chemoattractant protein-1 (MCP-1) were evaluated as markers of selectivity of the glomerular barrier and inflammation, respectively. Results. In relation to glomerular markers, all CVID patients had normal GFR (>90 mL/min/1.73 m2), and microalbuminuria and urinary MCP-1 levels were also similar to those of controls. Interestingly, CVID patients had reduced urinary concentration capacity, as demonstrated by lower U/POsm ratio, when compared to controls. Also, while all control subjects achieved a urinary pH less than 5.3, no CVID patients showed a decrease in urinary pH to such levels in response to acid loading with CaCl2, characterizing impaired urinary acidification capacity. Conclusion. Patients showed a trend towards an elevated prevalence of tubular dysfunction, mainly related to urinary acidification and concentration capacities.